PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DALAM PENERAPAN MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, DAN SATISFACTION) - Kiki Efendi (Department of Mathematics Education, Universitas Kuningan, 2016)
This article describes the influence of teachers' pedagogical understanding of mathematical abilities of vocational students in the application of learning models ARIAS (Assurance, Relevance, Interest, Assessment, and Satisfaction). The method used in this study is an experiment with a model of